A comparative analysis of children's time use and educational achievement: Assessing evidence from China, Japan and the United States. (April 2020) - Nakamura, Ryosuke; Yamashita, Jun; Akabayashi, Hideo; Tamura, Teruyuki; Zhou, Yang
Various forms of empirical evidence suggest that parental socioeconomic status (SES) is strongly related to educational outcomes and many countries attempt to close achievement gaps among children. Parenting practice is one important mechanism through which educational inequality emerges across families with different SES. In this paper, we show that the class gap in children's time use and academic achievements reflects parenting styles and parental practices stratified by parental SES by comparatively investigating the cases of China, Japan, and the USA, drawing on three sets of nationally representative longitudinal data. We find that for children aged 10–15 in China, parental SES has a strong impact on children's homework time and academic performance. Similar patterns are found in the results of 10–15-year-old children in Japan; however, homework time more weakly relates to the parents' education level. Moreover, restricting the samples to 14-year-old children and comparing the three countries, we find that the test score gap among parental SES is the largest in the USA; to fill the gap in math test scores between the first and fourth income quartiles, a sizable number of additional hours spent on homework are needed in the USA, compared to China and Japan.